Dampak Keberagaman Etnis terhadap Toleransi Mahasiswa dalam Konteks Pendidikan - Lilly Linne Anita Kainde; Jentelino Silvester Langitan; Glendy David Matindas; Gabriella Weena Putri Mapasa; Feebe Lineke Lumawir (LP. Ma'arif Janggan Magetan, 2024)
This study investigates the impact of ethnic diversity on the level of student tolerance in the context of education. Involving students with diverse ethnic backgrounds, a statistical analysis approach was used to evaluate the relationship between ethnic diversity and the level of tolerance in the university environment. The data obtained was then processed using the Structural Equation Modeling (SEM) approach using SmartPLS statistical software. The hypothesis in this study examines the impact of ethnic diversity on student tolerance. The results of the analysis stated that there was a significant impact and had a positive influence of ethnic diversity on the level of tolerance. The results of the research may provide important insights for the next research that will explore and deepen the variables of ethnic diversity.